Study on Mechanical Properties of the Basalt Fiber-Rubber Granular Concrete under Triaxial Stress Condition and Its Application - Duohua Wu; Zhiwen Li; Juli Li; Bo Peng; Hui Shen (Applied Sciences, 2020)
To reduce the failure probability of rigid supporting structures caused by large deformation of deeply buried high-stress soft rock roadways, the mechanical properties and failure features of basalt fiber-rubber granular concrete (BFRGC) are investigated based on triaxial compression tests. The post-peak strain softening equations of BFRGC, based on the Mohr–Coulomb yield criterion, are deduced and then compiled in the finite-difference software (FLAC3D) to simulate the post-peak strain-softening process of BFRGC. Combined with practical engineering, the supporting effects of BFRGC with different proportions are evaluated by FLAC3D. The results of compression tests show that the yield strength of the BFRGC increases significantly when the mass percentage of basalt fiber is 0.4%. Moreover, mixing basalt fibers into both the plain concrete and rubber concrete can effectively restrain the development of the fractures under three-dimensional stress. The numerical results show that when the mass fractions of basalt fibers and rubber particles are 0.4% and 5–10%, respectively, both the plastic zone in the surrounding rocks and the deformation of the rigid supporting structures decrease obviously. It is indicated that the optimal ratio of BFRGC can effectively reduce the stress concentration around the roadway and improve the overall bearing capacity of the supporting structures.